Photocatalytic degradation of phthalic anhydride and dicarboxylic acids - Ökte, Ayşe Neren. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1994., 1994)
Exposure of Ti02 particles to light with an energy equal or greater than its bandgap leads to the creation of electrons and holes which are able to degrade toxic chemicals. In this study, in the presence of Degussa P25 TiO2, photocatalytic oxidation of phthalic anhydride, malonic acid, succinic acid, and adipic acid has been investigated by means of gas chromatography techniques following the CO2 formation. The alteration of pH of the aqueous suspension, TiO2 loading, anhydride or acids concentrations, irradiation time, flow rate, and light intensity changed the rate of formation sf C02 which has been investigated by the same method. It was also observed that the rate of CO2 formation increases linearly by increasing the temperature sf the suspension. The order of the reactions as well as the rate constants could be determined for the photocatalpic oxidation processes. As a consequence, by altering the concentration of malonic, succinic, and adipic acids we observed that their disappearance fits a Langmuir-Hinshelwood kinetic model. In other words, the photoocatalytic xidation reactions take place in the adsorbed phase, i.e., on the surface of Ti02. Rate constants was also calculated by including the correction term a(T) which stands in order to take into account the decrease in the solubility of CO2 with increasing temperature. These results led to the calculation of activation energy as: 3.19 kj/mole, 9.99 kj/mole, 15.59 kj/mole, and 14.38 kj/mole for phthalic anhydride, malonic acid, succinic acid, and adipic acid respectively. Finally, 0.43X10 -6 quantum yield for the CQ formation has been estimated from the proposed mechanisms.
Keywords: Photochemistry.; Acids.; Photocatalysis.